RESPONS PERTUMBUHAN DAN PRODUKSI TANAMAN JAGUNG (Zea mays L.) VARIETAS NONHIBRIDA DAN HIBRIDA TERHADAP PEMBERIAN BOKASHI DAN PUPUK KALIUM - Reza Zulfahmi; Mbue Kata Bangun; Rosmayati r (Jurnal Agroekoteknologi, 2013)
Response on Growth and Yield of Maize  (Zea mays L.) Hybrid and Nonhybrid Varieties by Giving Bokashi and Potassium Fertilizer, a research had been conducted at experimental field of Balai Benih Induk Palawija, Tanjung Selamat, Kabupaten Deli Serdang, North Sumatera, Medan        (± 57 m asl) in May – August  2012. This research was arranged using randomized block design with treatment; nonhybrid varieties (Bisma) and hybrid varieties (SHS-4), bokashi with level 0 and 180 g/plant, potassium fertilizer with level 0, 1.8, and 3.6 g/plant, treatment was replicated three times, the data were analyzed with ANOVA and continued with HSD. The results showed that potassium fertilizer with 0 grams of Bokashi reached the maximum dose at 2.2 g/plant to nonhybrid varieties (Bisma) and hybrid varieties (SHS-4), while the addition of 180 g bokashi, potassium fertilizer reaches a maximum dose at 1.4 g/plant to nonhybrid varieties (Bisma) and 1.2 g/plant hybrid varieties (SHS-4) for a weight of 100 seeds. In the production of dry shelled potassium fertilizer by 180 g bokashi, nonhybrid varieties (Bisma) reached a maximum dose at 1.9 g/plant and 2.5 g/plant to hybrid varieties  (SHS-4).   Keywords: nonhybrid, hybrid, bokashi, potassium